Nonmagnetic and Magnetic Quantum Dots 2018
DOI: 10.5772/intechopen.74032
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Photosynthetic Productivity by Quantum Dots Application

Abstract: The challenge of climate change promotes use of carbon neutral fuels. Biofuels are made via fixing carbon dioxide via photosynthesis which is inefficient. Light trapping pigments use restricted light wavelengths. A study using the microalga Botryococcus braunii (which produces bio-oil), the bacterium Rhodobacter sphaeroides (which produces hydrogen), and the cyanobacterium Arthrospira platensis (for bulk biomass) showed that photosynthetic productivity was increased by up to 2.5-fold by upconverting unused wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…A study by Murray and coworkers demonstrated the use of zinc sulfide (ZnS) QDs in the biohydrogen production process, which resulted in around 1.1‐fold enhancement in the generation of biohydrogen in comparison to the PF process without using ZnS QDs. This was caused by the photoluminescence feature of the QDs, which allows solar light to be reformed by turning the inactive wavelengths into a usable wavelength where it can be used by the bacteriochlorophylls for the photosynthesis process 127 . The PNSB are essentially active and utilize light energy under the near‐infrared range between wavelengths 790 nm to 940 nm.…”
Section: The Significant Role Of Nanomaterials In Biofuel Productionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by Murray and coworkers demonstrated the use of zinc sulfide (ZnS) QDs in the biohydrogen production process, which resulted in around 1.1‐fold enhancement in the generation of biohydrogen in comparison to the PF process without using ZnS QDs. This was caused by the photoluminescence feature of the QDs, which allows solar light to be reformed by turning the inactive wavelengths into a usable wavelength where it can be used by the bacteriochlorophylls for the photosynthesis process 127 . The PNSB are essentially active and utilize light energy under the near‐infrared range between wavelengths 790 nm to 940 nm.…”
Section: The Significant Role Of Nanomaterials In Biofuel Productionmentioning
confidence: 99%
“…The PNSB are essentially active and utilize light energy under the near‐infrared range between wavelengths 790 nm to 940 nm. Hence, the properties of QDs, such as wavelength absorbance and emissions, may be changed and varied by altering the synthesis parameters, which can allow the use of size‐modified QDs with optical properties that favor the growth of PNSB and consecutively the PFB generation process 127,128 …”
Section: The Significant Role Of Nanomaterials In Biofuel Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…The above discussion indicates that the energy products generated by the thermalhydrolysis of cellulose (model compound used in this work) are currently incapable to provide, at the least, the energy needed for the overall process. In addition, in the valorisation of real lignocellulosic wastes, cellulose extraction from lignocellulosic biomass requires high 'parasitic' energy demand of upstream comminution, which is required to obtain a suitable particle size for cellulose extraction, which can then be efficiently achieved via delignification using environmentally friendly thermal subcritical water-ethanol-CO 2 mediated hydrolysis (P initial 55 bar; T final 200 • C) [58,59]. Nontrivially, the energy consumption to mill Miscanthus (moisture content of 15%) to <4 mm was 184 kJ/kg of dry matter [60], which can be compared to a hydrogen energy content of only 10 kJ/litre at 1 atm and 15 • C and, hence, 18.4 L of H 2 would be 'consumed' per kilo of Miscanthus source material.…”
Section: Key Factors In Waste Up-valorisation: Towards An Integrated ...mentioning
confidence: 99%